2013
DOI: 10.1038/nature12539
|View full text |Cite
|
Sign up to set email alerts
|

Observing single quantum trajectories of a superconducting quantum bit

Abstract: The length of time that a quantum system can exist in a superposition state is determined by how strongly it interacts with its environment. This interaction entangles the quantum state with the inherent fluctuations of the environment. If these fluctuations are not measured, the environment can be viewed as a source of noise, causing random evolution of the quantum system from an initially pure state into a statistical mixture--a process known as decoherence. However, by accurately measuring the environment i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
522
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(531 citation statements)
references
References 27 publications
7
522
2
Order By: Relevance
“…To mitigate these effects, we actively feedback to stabilize the Rabi frequency to within 10 kHz and suppress leakage of the local oscillator used to generate the sidebands to the 10 −4 photon level. Because a single SQM commutes with itself at all times, the integral of the signal fully specifies the amount of projection onto an eigenstate 18 . We perform tomographic state validation on subsets of the data post-selected according to this integrated signal.…”
Section: Figmentioning
confidence: 99%
“…To mitigate these effects, we actively feedback to stabilize the Rabi frequency to within 10 kHz and suppress leakage of the local oscillator used to generate the sidebands to the 10 −4 photon level. Because a single SQM commutes with itself at all times, the integral of the signal fully specifies the amount of projection onto an eigenstate 18 . We perform tomographic state validation on subsets of the data post-selected according to this integrated signal.…”
Section: Figmentioning
confidence: 99%
“…Following the path of Yurke's et al work in the late 1980s [1][2][3], several designs of Josephson junction-based parametric amplifiers (JPAs) have been introduced [4][5][6][7][8][9][10][11]. In addition to high-fidelity superconducting qubit readout leading to the observation of quantum jumps [12,13], this new generation of near quantumlimited amplifiers have opened up new experimental possibilities such as the creation and tomography of squeezed microwave light [14][15][16], and detailed weak measurement experiments [17][18][19]. JPAs are now ubiquitous in current superconducting circuit experiments, and applications in other research communities are growing [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of JPAs as a source of squeezed light are therefore intimately related to their noise properties as a phase-sensitive amplifier. While JPAs are usually modeled as quantum-limited amplifiers, and thus perfect squeezers, experimental results indicate that nonidealities limits both the achievable level of squeezing [28][29][30] and the measurement quantum efficiency [17,29,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…See Refs. [11,12] for recent experiments using this interaction. This name "light shift" is related to a Hamiltonian of the form…”
Section: Implementationsmentioning
confidence: 99%
“…Notably, this example is a variation of the original weak value amplification scenario [1], but using a different parameter regime that more commonly appears in cavity and circuit QED [11,12]. Even though the coherent state used in their example is typically considered to be a classical quantity that does not provide quantum resources, the authors showed the surprising result that the Fisher information about the coupling parameter seemed to scale at the optimal Heisenberg limit as the average number of photons was increased, rather than at the standard quantum limit that one would typically expect.…”
Section: Introductionmentioning
confidence: 99%